Lynch syndrome–associated urothelial carcinoma: clinical and molecular findings from a single-institution cohort - A. Rametta; M. Barella; A. Scardino; F. Barbetta; E. Tamborini; F. Perrone; A. Busico; L. Agnelli; S. Rota; E. Gusmaroli; M. Stellato; A. Nuzzo; et al. (Familial Cancer, 2026)

Interpreting Fentanyl and Norfentanyl Concentrations among Patients Seen in the Emergency Department after a Nonfatal Opioid Overdose: A Multicenter Study - Jessica T. Kent; Rachel Culbreth; Jacob A. Lebin; Keith Burkhart; Robert G. Hendrickson; Zachary D. W. Dezman; Kim Aldy; Jeffrey Brent; Alyssa Falise; Sharan Campleman; Barry K. Logan; Michael Levine; et al. (Journal of Medical Toxicology, 2026)

Progress status of the NUSES Space Mission - M. Abdullahi; R. Aloisio; S. Ashurov; U. Atalay; F.C.T. Barbato; R. Battiston; M.E. Bertaina; E. Bissaldi; D. Boncioli; L. Burmistrov; I. Cagnoli; E. Casilli; et al. (Advances in Space Research, 2026)

Early effects of anti-TNFα antibodies in horses with osteoarthritis - G. Perrone; C. Giampaoli; A. Lorenzo Smirnoff; A. Ochoa; R. Pareja; E. De Simone (Journal of Equine Veterinary Science, 2025)

Integrated geophysical and geological surveys reveal new details of the large Montescaglioso (southern Italy) landslide of December 2013 - G. Calamita; M.R. Gallipoli; E. Gueguen; R. Sinisi; V. Summa; L. Vignola; T.A. Stabile; J. Bellanova; S. Piscitelli; A. Perrone (Engineering Geology, 2023)

Seismic risk assessment of masonry-infilled RC building portfolios: impact of variability in the infill properties - G. Mucedero; D. Perrone; R. Monteiro (Bulletin of Earthquake Engineering, 2023)

Electrochemotherapy of skin metastases from malignant melanoma: a PRISMA-compliant systematic review - Martina Ferioli; Valentina Lancellotta; Anna Myriam Perrone; Alessandra Arcelli; Andrea Galuppi; Lidia Strigari; Milly Buwenge; Francesca De Terlizzi; Silvia Cammelli; Roberto Iezzi; Pierandrea De Iaco; Luca Tagliaferri; et al. (Clinical & Experimental Metastasis, 2022)
The main treatment of MM metastases are systemic therapies, surgery, limb perfusion, and intralesional talimogene laherparepvec. Electrochemotherapy (ECT) is potentially useful also due to the high response rates recorded in cancers of any histology. No randomized studies comparing ECT with other local therapies have been published on this topic. We analyzed the available evidence on efficacy and toxicity of ECT in this setting. PubMed, Scopus, and Cochrane databases were screened for paper about ECT on MM skin metastases. Data about tumor response, mainly in terms of overall response rate (ORR), toxicity (both for ECT alone and in combination with systemic treatments), local control (LC), and overall survival (OS) were collected. The methodological quality was assessed using a 20-item validated quality appraisal tool for case series. Overall, 18 studies were included in our analysis. In studies reporting “per patient” tumor response the pooled complete response (CR) was 35.7% (95%CI 26.0–46.0%), and the pooled ORR was 80.6% (95%CI 68.7–90.1%). Regarding “per lesion” response, the pooled CR was 53.5% (95%CI 42.1–64.7%) and the pooled ORR was 77.0% (95%CI 56.0–92.6%). One-year LC rate was 80%, and 1-year OS was 67–86.2%. Pain (24.2–92.0%) and erythema (16.6–42.0%) were the most frequent toxicities. Two studies reported 29.2% and 41.6% incidence of necrosis. ECT is effective in terms of tumor response and tolerated in patients with skin metastases from MM, albeit with a wide variability of reported results. Therefore, prospective trials in this setting are warranted.

A Brief Educational Intervention to Increase ED Initiation of Buprenorphine for Opioid Use Disorder (OUD) - Utsha G. Khatri; Kathleen Lee; Theodore Lin; Joseph L. D’Orazio; Mitesh S. Patel; Frances S. Shofer; Jeanmarie Perrone (Journal of Medical Toxicology, 2022)

Nonlinear static characterisation of masonry-infilled RC building portfolios accounting for variability of infill properties - G. Mucedero; D. Perrone; R. Monteiro (Bulletin of Earthquake Engineering, 2021)

Physical stratigraphy and geotechnical properties controlling the local seismic response in explosive volcanic settings: the Stracciacappa maar (central Italy) - M. Moscatelli; G. Vignaroli; A. Pagliaroli; R. Razzano; A. Avalle; I. Gaudiosi; S. Giallini; M. Mancini; M. Simionato; P. Sirianni; G. Sottili; J. Bellanova; et al. (Bulletin of Engineering Geology and the Environment, 2021)
Nowadays, policies addressed to prevention and mitigation of seismic risk need a consolidated methodology finalised to the assessment of local seismic response in explosive volcanic settings. The quantitative reconstruction of the subsoil model provides a key instrument to understand how the geometry and the internal architecture of outcropping and buried geological units have influence on the propagation of seismic waves. On this regard, we present a multidisciplinary approach in the test area of the Stracciacappa maar (Sabatini Volcanic District, central Italy), with the aim to reconstruct its physical stratigraphy and to discuss how subsoil heterogeneities control the 1D and 2D local seismic response in such a volcanic setting. We first introduce a new multidisciplinary dataset, including geological (fieldwork and log from a 45-m-thick continuous coring borehole), geophysical (electrical resistivity tomographies, single station noise measurements, and 2D passive seismic arrays), and geotechnical (simple shear tests performed on undisturbed samples) approaches. Then, we reconstruct the subsoil model for the Stracciacappa maar in terms of vertical setting and distribution of its mechanical lithotypes, which we investigate for 1D and 2D finite element site response analyses through the application of two different seismic scenarios: a volcanic event and a tectonic event. The numerical modelling documents a significant ground motion amplification (in the 1–1.5 Hz range) revealed for both seismic scenarios, with a maximum within the centre of the maar. The ground motion amplification is related to both 1D and 2D phenomena including lithological heterogeneity within the upper part of the maar section and interaction of direct S-waves with Rayleigh waves generated at edges of the most superficial lithotypes. Finally, we use these insights to associate the expected distribution of ground motion amplification with the physical stratigraphy of an explosive volcanic setting, with insights for seismic microzonation studies and local seismic response assessment in populated environments.

The microRNA-29a Modulates Serotonin 5-HT7 Receptor Expression and Its Effects on Hippocampal Neuronal Morphology - Floriana Volpicelli; L. Speranza; S. Pulcrano; R. De Gregorio; M. Crispino; C. De Sanctis; M. Leopoldo; E. Lacivita; U. di Porzio; G. C. Bellenchi; C. Perrone-Capano (Molecular Neurobiology, 2019)

Seismic performance of non-structural elements during the 2016 Central Italy earthquake - D. Perrone; P. M. Calvi; R. Nascimbene; E. C. Fischer; G. Magliulo (Bulletin of Earthquake Engineering, 2019)

Delivery of Brain-Derived Neurotrophic Factor by 3D Biocompatible Polymeric Scaffolds for Neural Tissue Engineering and Neuronal Regeneration - T. Limongi; A. Rocchi; F. Cesca; H. Tan; E. Miele; A. Giugni; M. Orlando; M. Perrone Donnorso; G. Perozziello; Fabio Benfenati; Enzo Di Fabrizio (Molecular Neurobiology, 2018)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Contribution of EARLINET/ACTRIS to the summer 2013 Special Observing Period of the ChArMEx project: monitoring of a Saharan dust event over the western and central Mediterranean - M. Sicard; R. Barragan; C. Muñoz-Porcar; A. Comerón; M. Mallet; F. Dulac; J. Pelon; L. Alados Arboledas; A. Amodeo; A. Boselli; J. A. Bravo-Aranda; G. D’amico; et al. (International Journal of Remote Sensing, 2016)

Spin-off Extreme Value and Archimedean copulas for estimating the bivariate structural risk - R. Pappadà; E. Perrone; F. Durante; G. Salvadori (Stochastic Environmental Research and Risk Assessment, 2016)

Columnar and ground-level aerosol optical properties: sensitivity to the transboundary pollution, daily and weekly patterns, and relationships - M. R. Perrone; S. Romano; J. A. G. Orza (Environmental Science and Pollution Research, 2015)

Determination of aerosol deliquescence and crystallization relative humidity for energy saving in free-cooled data centers - L. Ferrero; L. D’Angelo; G. Rovelli; G. Sangiorgi; M. G. Perrone; M. Moscatelli; M. Casati; V. Rozzoni; E. Bolzacchini (International Journal of Environmental Science and Technology, 2015)

Semivolatile PAH and n-alkane gas/particle partitioning using the dual model: up-to-date coefficients and comparison with experimental data - G. Sangiorgi; L. Ferrero; M. G. Perrone; E. Papa; E. Bolzacchini (Environmental Science and Pollution Research, 2014)

GIS and geomatics for disaster management and emergency relief: a proactive response to natural hazards - M. Giardino; L. Perotti; M. Lanfranco; G. Perrone (Applied Geomatics, 2012)

Cystic fibrosis Δf508 mutation screening in Brazilian women with altered fertility - G. V. F. Brunoro; E. V. Wolfgramm; I. D. Louro; I. I. Degasperi; V. C. W. Busatto; A. M. S. Perrone; M. C. P. Batitucci (Molecular Biology Reports, 2011)

Post-collisional tectonics in the Northern Cottian Alps (Italian Western Alps) - G. Perrone; P. Cadoppi; S. Tallone; G. Balestro (International Journal of Earth Sciences, 2011)

Morphological and biological characterization of cell line developed from bovine Echinococcus granulosus - Claudia I. Echeverría; Dora M. Isolabella; Elio A. Prieto Gonzalez; Araceli Leonardelli; Laura Prada; Alina Perrone; Alicia G. Fuchs (In Vitro Cellular & Developmental Biology - Animal, 2010)

Developmental stages of attachment of in vitro protoplasts in two Mediterranean Valonia species (Siphonocladales, Chlorophyta) - A. Bottalico; G. P. Felicini; C. I. Delle Foglie; C. Perrone (Plant Biosystems, 2008)

A Biomonitoring Study Assessing the Residual Biological Effects of Pollution Caused by the HAVEN Wreck on Marine Organisms in the Ligurian Sea (Italy) - A. Viarengo; F. Dondero; D. M. Pampanin; R. Fabbri; E. Poggi; M. Malizia; C. Bolognesi; E. Perrone; E. Gollo; G. P. Cossa (Archives of Environmental Contamination and Toxicology, 2007)

Neonatal pain analyzer: development and validation - R. Sisto; C. V. Bellieni; S. Perrone; G. Buonocore (Medical & Biological Engineering & Computing, 2006)

Identification, incidence and characterization of Fusarium proliferatumon ornamental palms in Spain - J. Armengol; A. Moretti; G. Perrone; A. Vicent; J.A. Bengoechea; J. García-Jiménez (European Journal of Plant Pathology, 2005)

PCR Assay for Identification of Aspergillus Carbonarius and Aspergillus Japonicus - G. Perrone; A. Susca; G. Stea; G. Mulè (European Journal of Plant Pathology, 2004)

Molecular and Biochemical Characterization of Two Atypical Toxigenic Populations of Fusarium Camptoceras - G. Mule’; C. Altomare; A. Moretti; G. Perrone; A. Logrieco (Cereal Research Communications, 1997)

Fusapyrone and Deoxyfusapyrone from Fusarium semitectumi Production and Biological Activities - C. Altomare; G. Perrone; M. C. Zonno; L. Polonelli; A. Evidente (Cereal Research Communications, 1997)